1998
DOI: 10.2337/diacare.21.7.1071
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of the Incidence of and Predictive Risk Factors for Diabetic Neuropathic Foot Ulceration

Abstract: Tests of VPT and Michigan DPN scores for muscle strength and reflexes are useful clinical predictors for foot ulceration in diabetic patients with established neuropathy. The rate of subsequent ulceration in the following year was alarmingly high, however, despite standardized foot care education at baseline and regular follow-up visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
216
2
24

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(260 citation statements)
references
References 19 publications
8
216
2
24
Order By: Relevance
“…O LPV, sensível para diagnóstico de neuropatia leve e subclínica (20), já tinha sido apontado por Boulton e cols. (21) (12). Os autores observaram que a cada aumento de 1 volt no LPV o risco da primeira úlcera no pé se elevava em 5,6%.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O LPV, sensível para diagnóstico de neuropatia leve e subclínica (20), já tinha sido apontado por Boulton e cols. (21) (12). Os autores observaram que a cada aumento de 1 volt no LPV o risco da primeira úlcera no pé se elevava em 5,6%.…”
Section: Discussionunclassified
“…Outros estudos confirmaram o ponto de corte do LPV ≥ 25 volt como preditivo para ulceração do pé (10,11). Cada aumento de 1 volt da LPV no nível basal de percepção do indivíduo associou-se a aumento de 5,6% no risco de úlcera (12).…”
Section: Introductionunclassified
“…Two studies from northern European countries reported the annual incidence of foot ulcers in the general diabetes population to be just over 2% [12,13]. Ulceration is much more common in patients with predisposing risk factors; annual incidence rates in neuropathic individuals vary from 5% to over 7% [18,19]. It is likely that more than 5% of diabetic patients have a history of foot ulcers [11], whereas the cumulative lifetime incidence may be as high as 15% [9].…”
Section: Epidemiologymentioning
confidence: 99%
“…The association between both somatic and autonomic neuropathy and foot ulceration has been recognised for many years [35]. It is only in the last decade that prospective follow-up studies have confirmed this causative role of somatic neuropathy [12,18,19]. Patients with sensory loss appear to show an increase in risk of developing foot ulcers of up to seven-fold, compared with non-neuropathic diabetic individuals.…”
Section: Causal Pathways To Foot Ulcerationmentioning
confidence: 99%
“…A avaliação dos pés constitui-se em passo fundamental na identificação dos fatores de risco que podem ser modificados, o que, conseqüen-temente, reduzirá o risco de ulceração e amputação de membros inferiores nas pessoas com diabetes (30) . Autores destacam que a diminuição da sensação protetora, caracterizada pela redução da sensação dolorosa de trauma na pele (3,(32)(33)(34)(35)(36)(37) , bem como a ausência parcial ou total do reflexo Aquileu (14,26,(38)(39) constituem sinais precoces de futuros processos ulcerativos nos pés, significando alto risco para o desenvolvimento de complicações. Ambas as alterações podem ser avaliadas mediante testes que utilizam vários tipos de instrumentos, desde os mais sofisticados aos mais simples.…”
Section: Avaliação Dos Pés E Prevenção De Complicaçõesunclassified